How do you solve for y in the equation 2x + y = 6?

We have to solve for y for the equation 2x+y=6

Solution

2x+y=6

Shifting 2x to RHS we get

y=6-2x

Similarly to solve for x

Simplifying
2x + y = 6

Solving
2x + y = 6

Solving for variable ‘x’.

Move all terms containing x to the left, all other terms to the right.

Add ‘-1y’ to each side of the equation.
2x + y + -1y = 6 + -1y

Combine like terms: y + -1y = 0
2x + 0 = 6 + -1y
2x = 6 + -1y

Divide each side by ‘2’.
x = 3 + -0.5y

Simplifying
x = 3 + -0.5y

Answer

For the equation 2x+y=6

x = 3 + -0.5y

y=6-2x

Leave a Comment

Your email address will not be published. Required fields are marked *

BOOK

Free Class